Evidence of Food Preparation, Consumption and Storage in a Late Medieval Manor in Czechowice, Upper Silesia - Radosław Zdaniewicz; Renata Abłamowicz (Fasciculi Archaeologiae Historicae)
While researching the late medieval manor house in Czechowice, a small number of discoveries were made that directly or indirectly represent traces of food preparation, consumption and storage by the inhabitants of the local settlement. Archaeobotanical and archaeozoological remains and movable material were analysed, and archaeological structures representing the remains of buildings were uncovered. They indicate that the inhabitants of the Czechowice Manor were engaged in cereal cultivation and animal husbandry, which provided the local table with vegetable and meat and dairy products. Unfortunately, it has not been possible to discover the specific place where the food was prepared, but it seems that it was outside the residential part of the manor, perhaps in the open air or within an above-ground building with a light structure. The discovered storage pits or individual objects indicate that the Czechowice manor both stored and preserved meat or other products in a natural manner. It is difficult to create a complete picture of the sphere of life that constituted the consumption, preparation and storage of food by the inhabitants of the manor, however, they are certainly an interesting and important example for comparative studies with other late medieval settlement sites of this type.